2000
DOI: 10.1016/s0304-3959(99)00253-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and phases of the estrous cycle alter the response of spinal cord dynorphin neurons to peripheral inflammation and hyperalgesia

Abstract: The neuromodulatory interactions of sex steroids with the opioid system may result in sex differences in pain and analgesia. Dynorphin is an endogenous kappa-opioid peptide that is upregulated in an animal model of peripheral inflammation and hyperalgesia and is possibly regulated by circulating levels of sex steroids. The present study compared behavioral responses of male, cycling female, and gonadectomized Sprague-Dawley rats in a model of persistent pain. Cycling female rats were behaviorally tested over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 23 publications
8
51
0
Order By: Relevance
“…The result is compatible with previously reported epidemiologic studies in human populations (6,8,38) and laboratory experiments in animals (1,3,7,17,34,35) showing that the female is highly sensitive to noxious stimuli and pain. On the other hand, our present results suggest the possibility that the male urethra is affected more evidently.…”
Section: Ajp-regul Integr Comp Physiolsupporting
confidence: 92%
“…The result is compatible with previously reported epidemiologic studies in human populations (6,8,38) and laboratory experiments in animals (1,3,7,17,34,35) showing that the female is highly sensitive to noxious stimuli and pain. On the other hand, our present results suggest the possibility that the male urethra is affected more evidently.…”
Section: Ajp-regul Integr Comp Physiolsupporting
confidence: 92%
“…Thresholds were lower in nonarthritic rats during proestrus and in arthritic rats thresholds were lower during estrus and proestrus. Although a definitive conclusion regarding the influence of circulating hormones cannot be made, these results complement those demonstrating greater thermal hyperalgesia in arthritic rats during the proestrus phase (Bradshaw et al, 2000).…”
Section: Discussionsupporting
confidence: 66%
“…Evidence has shown that estrogen affected chronic inflammation [9,10]. We then investigated the effect of estrogen on OVX CFA rats.…”
Section: Estrogen Replacement Reversed the Decrease Of Pwt In Ovariecmentioning
confidence: 99%
“…Mechanical hyperalgesia and allodynia in the abdomen, hind limbs, and proximal tail of OVX rats, which result from a lack of estrogen in the body, can be reversed by sustaining exogenous estradiol replacement [8]. During several days or weeks after inflammation or injury, estrogen promotes the development of heat hyperalgesia and mechanical hyperalgesia [9,10]. The estrogen effects depend on the type, time course of pain or inflammation models, and also the level and stability of estrogens [7].…”
Section: Introductionmentioning
confidence: 99%